Is the judge really a poet? A few words aloud about the recent anthology «Judges in Chilean Literature» by Aristotle Spain - Coaguila Valdivia, Jaime Francisco (2008)
Starting from the anthology «Judges in the Chilean Literature» (2006) by the writer Aristóteles España, the question arises as to whether it is possible to build a model of «literary judge» within the Latin American context, to then examine the legal imagination and personal narratives in the literature of Chilean judges, making a comparison with the Peruvian judge and poet Enrique López Albújar,  and concluding with the proposal of a judicial poetics based on alterity.